Analysis of cumulative antibiogram reports in intensive care units at an Egyptian University Hospital - Essamedin M. Negm; Eman S. Elgharabawy; Shahenda G. Badran; ALZahraa M. soliman; Aya M. el sayed; Aya O.N. Raafat; Sara T. Soliman; Heba M. Mahmoud; Ahmed E. Tawfik; Amr T. EL Hawary; Abeer El Hawary; Ahmed Elhewala; et al. (Elsevier, 2023)
Background: Institutions must have access to antibiograms to monitor changes in antimicrobial resistance and direct empirical antibiotic therapy. The first facility-specific cumulative antibiogram was launched in the ICU in 2019. Consequently, many antibiogram-operation-related actions have been adopted in the institution based on reported data. This study aimed to analyze the cumulative antibiogram reports for multiple intensive care units (ICUs) for 2020, and compare the antimicrobial susceptibility testing (AST) patterns between the 2019 and 2020 years in an academic medical center. Methods: This cross-sectional study was performed of routine bacterial culture and AST data extracted from a laboratory information system in a 2252-bed capacity hospital. Only the first diagnostic isolate of a given species per patient per year was included in the study. Interpretation and reporting were done in accordance with the applicable Clinical and Laboratory Standards Institute and European Committee on Antimicrobial Susceptibility Testing guidelines. Results: Of the 46,791 clinical isolates, the Gram-negative bacilli isolation rate witnessed a significant increase: 35,670 isolates in 2020 versus. 33,652 isolates in 2019. Klebsiella pneumoniae showed a statistically significant increase, mainly in pediatric, emergency, and cardiothoracic ICUs (p < 0.001). Neonatal and pediatric ICUs showed statistically significant increases in Pseudomonas aeruginosa and Proteus mirabilis isolates (p < 0.001). A statistically significant decrease was noted in the prevalence of Acinetobacter, Escherichia coli, Burkholderia cepacia, and Enterobacter cloacae. The sensitivities of K. pneumoniae and E. coli to imipenem and tigecycline significantly improved (p < 0.001). The sensitivity to colistin was significantly decreased (p < 0.001). The sensitivity of P. aeruginosa isolates to colistin and carbapenems was improved (p < 0.001). We reported a statistically significant decrease in all Gram-positive cocci (11,121 in 2020 versus. 11,528 in 2019). Staphylococcus aureus showed a statistically significant increase (p < 0.001), particularly in the medical ICU. Conclusion: The high susceptibility rates of Enterobacteriaceae toward colistin and tigecycline, should be cautiously considered in empiric therapy while looking for alternatives. The majority of isolates of Gram-positive cocci were coagulase negative staphylococci (CONS), we still need to confirm whether they are true pathogens or commensals before considering anti-staphylococcal agents in the empirical therapy. We underscored some corrective actions that might have improved the susceptibility rates, such as antibiotic cycling